Cloud security: Emerging threats and current solutions. (April 2017) - Coppolino, Luigi; D'Antonio, Salvatore; Mazzeo, Giovanni; Romano, Luigi
Abstract: Many organizations are stuck in the cloudify or not to cloudify limbo, mainly due to concerns related to the security of enterprise sensitive data. Removing this barrier is a key pre-condition to fully unleash the tremendous potential of cloud computing. In this paper, we provide a comprehensive analysis of the main threats that hamper cloud computing adoption on a wide scale, and a right to the point review of the solutions that are currently being provided by the major vendors. The paper also presents the (near) future directions of cloud security research, by taking a snapshot of the main research trends and most accredited approaches. The study is done on a best of breed selection of proprietary and Open Source cloud offerings. The paper is thus a useful navigation tool, that can be used by the IT personnel to gain more insight into the security risks related to the use of cloud computing, as well as to quickly weigh the pros and cons of state of the art solutions.